Binding of STEVOR protein to various receptor on erythrocytes - Chua, Zong Sheng (2017)
Malaria is currently one of the most life-threatening infectious disease that affects any individual located along the equator of the earth. With so many new cases and high mortality rate, studies have been carried out to find out the reason behind the severity of malaria. Results from these studies have showed that expression of different variant surface antigens does contributes to severity of the disease. The pathogenesis of malaria is due to the expression of variant surface antigen by the parasite known as Plasmodium falciparum. 3 families of variant surface antigen, expressed by Plasmodium falciparum, are PfEMP1, RIFINs and STEVORs. With many of the variant surface antigen not fully understood, there could be novel functions yet to be discovered. In this project, recombinant STEVOR protein are expressed and tested with protease-treated red blood cells so to characterize possible receptors which may have interactions with STEVORs. The results have showed that different IPTG concentration as well as incubation conditions can affect the expression of recombinant STEVOR proteins in transformed cells. Expressed STEVORs may not be folded correctly which could hinder the protein purification process. Results of the western blot analysis confirm that STEVORs interact with glycophorin C on the red blood cells. One STEVOR manages to produce a unique result that is different from other STEVORs that were used for erythrocytes binding assays. Glycophorin C are sensitive to trypsin and neuraminidase treatment while resistant to chymotrypsin treatment Semi-conserved region of STEVOR protein binds to glycophorin C to facilitate adhesion to the vasculature or mediate PfEMP-1-independent rosetting which are important for the pathogenesis of malaria. However, one of the STEVOR protein may interactions with receptors other than glycophorin C on the red blood cells. Binding to different receptors may lead to the activation of other chemical reactions that could contribute to the pathogenicity of the infectious disease.